Working with Nonprofit Organizations in Community Settings: Governance, Board Officer Descriptions - Elizabeth B. Bolton; Anna Guest-Jelley (EDIS, 2009)
This is part of a series of 2-5 page fact sheets by Elizabeth B. Bolton and Anna Guest-Jelley that provide guidance for building a non-profit organization, from establishing its mission to effectively lobbying. Includes references. Published by the UF Department of Family Youth and Community Sciences, June 2009. Reviewed June 2012.